Acrokeratosis verruciformis of Hopf in family - Sanjay N Agrawal; Subodhkumar D Jane; Anuprita A Rawal (Wolters Kluwer Medknow Publications, 2014)
Acrokeratosis verruciformis of Hopf (AKV) is a rare disorder of keratinization inherited in an autosomal dominant fashion. A 15-year-old female presented with numerous skin-colored papular lesions over the neck as well as dorsa of the hands and feet of 7 years duration. Similar lesions were noted in her mother. Six other members of her family showed similar lesions with similar site of involvement. Presence of characteristic warty papules and histopathology led to diagnosis of a rare condition of acrokeratosis verruciformis.